Comparative Assessment of Low-GWP Based Refrigerating Plants Operating in Hot Climates. (March 2017) - Purohit, Nilesh; Gullo, Paride; Dasgupta, Mani Sankar
Abstract: Carbon dioxide (CO2 or R744) and HFO-1234ze(E) are two promising alternatives to the currently employed high-GWP working fluids for food retail applications. In this paper, two indirect refrigeration systems using respectively R1234ze(E) and CO2 as the primary and the secondary fluid, a R744 booster configuration with parallel compression and a R744 booster solution with R290 dedicated mechanical sub-cooling are theoretically compared with a R404A multiplex direct expansion refrigerating system (baseline). The latter serves both the LT and the MT load. All the evaluated configurations are supposed to be for commercial refrigeration technologies. The results in terms of COP reveal that both the investigated "CO2 only" configurations have the best performance at low outdoor temperatures. On the other hand, the indirect solutions can outperform all the selected refrigerating plants at the extreme climatic conditions. In comparison with the baseline, a maximum reduction in annual electricity consumption by 6.4% and 8.9% is observed for R1234ze(E) and CO2 based systems, respectively.